Understanding the common mistakes made by Fundamentals of Computer Problem Solving (CSC128) students of Universiti Teknologi MARA Cawangan Pulau Pinang, Malaysia on repetition and functions topic / Wan Anisha Wan Mohammad, Naemah Abdul Wahab and Azlina Mohd Mydin - Wan Mohammad, Wan Anisha; Abdul Wahab, Naemah; Mohd Mydin, Azlina (Unit Penerbitan JSKM, 2020)
Computer programming is the process of writing and designing a computer programs while a computer program is a set of instructions to solve problems (Anisha et. al., 2019). Learning computer programs need to start from the basic level before anyone can go to a higher level. Thus, it is very important for non-programmers to understand the basic concepts of programming before they are able to solve a complicated one. Rogalski and Samurcay (1990) summarise in their study that the process of acquiring and developing computer programming knowledge includes numerous cognitive activities and mental representations associated with program design, program comprehension, program debugging, program modifying and lastly program documentation. They added that programmers should be able to construct the theoretical understanding into schemas and plans using basic control structures such as conditional statements, loops, functions and others. Other than that, a study by Saeli et. al. (2011) mentioned that Govender (2006) indicated three main parts of learning to program are the data, instruction and syntax. Data refers to the variables and data types of a computer language while instruction is the control structures (conditional statements, loops and others) and subroutines in the programming. Syntax represents the rules and vocabulary of a programming language.